MENDORONG KEMANDIRIAN EKONOMI DESA KUANHEUN DENGAN PENGELOLAAN BUMDES - Beatrix Yunarti Manehat; Enike Tje Yustin Dima (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
BUMDes in Kuanheun Village are still focused on savings and loans only, even though they has tourism potential. Poor management of the savings and loan business has an impact on BUMDes not being optimal in carrying out its role as a driving force for the village economy. With the problems above, this community service is carried out to provide understanding to village officials and the community about managing a savings and loan business and exploring tourism potential to be used as new business that can encourage community economic independence. This was carried out using the lecture and discussion method with 30 village officials and the community. The results show that village officials and the community have an understanding of the procedure for applying for a savings loan (starting from a savings and loan application until analyzing the eligibility of a loan) and how to monitor it. Furthermore, with the SWOT analysis, in the future the village government will maximize BUMDes for the development of tourist villages. The government plans to allocate the BUMDes budget for infrastructure improvements in tourist rides such as beaches and caves and allow the community to open MSMEs as a source of income. The village government will also actively cooperate with academics to provide training to village officials who are entrusted with the task of managing so that BUMDes can become a driver of the community's economy. The active participation of the community in overseeing the running of BUMDes can also be the key to the success of economic independence.